INFLUENCE OF ALPHA-1-ACID GLYCOPROTEIN UPON PRODUCTION OF CYTOKINES BY PERIPHERAL BLOOD MONONUCLEARS - М. V. Osikov; L. V. Krivohizhina; E. V. Makarov; V. Yu. Akhmatov (Медицинская иммунология, 2014)
Abstract. Alpha-1-acid glycoprotein (orosomucoid) is a multifunctional acute phase reactant belonging to the family of lipocalines from plasma alpha-2 globulin fraction. In present study, we investigated dosedependent effects of orosomucoid upon secretion of IL-1â, IL-2, IL-3, IL-4 by mononuclear cells from venous blood of healthy volunteers. Mononuclear cells were separated by means of gradient centrifugation, followed by incubation for 24 hours with 250, 500, or 1000 mcg of orosomucoid per ml RPMI-1640 medium (resp., low, medium and high dose). The levels of cytokine production were assayed by ELISA technique. Orosomucoid-induced secretion of IL-1â and IL-4 was increased, whereas IL-3 secretion was inhibited. IL-2 production was suppressed at low doses of orosomucoid, and stimulated at medium and high doses. The effect of alpha-1-acid glycoprotein upon production of IL-2, IL-3 and IL-4 was dose-dependent. Hence, these data indicate that orosomucoid is capable of modifying IL-1â, IL-2, IL-3, and IL-4 secretion by blood mononuclear cells.